Lethal toxin–equipped effector cells for the potential treatment of cancer - Alexander H. Pearlman; Brian J. Mog; Michael S. Hwang; Jordina Rincon-Torroella; Sarah R. DiNapoli; Suman Paul; Jacqueline Douglass; Emily Han-Chung Hsiue; Stephanie A. Glavaris; Drew M. Pardoll; Nickolas Papadopoulos; Kenneth W. Kinzler; et al. (Proceedings of the National Academy of Sciences, 2026)
Lethal toxins could become potent therapies against cancer, but their clinical utility is limited by adverse events upon systemic administration. These could be reduced if the toxins were delivered by effector cells that specifically infiltrate cancers, thereby releasing toxins locally into the tumor microenvironment. One of the challenges underlying this strategy is that cells delivering toxins would have to be resistant to them. We address this obstacle by showing that effectors derived from transformed human cell lines genetically engineered for resistance to bacterial adenosine diphosphate ribosylating toxins (ADPRTs), including Pseudomonas aeruginosa exotoxin A (PE), can produce targeted immunotoxins that specifically kill cancer cells expressing cognate tumor-associated antigens. Resistance to immunotoxins was achieved by knockout of genes in the diphthamide biosynthesis pathway ( DPH1-4 ) required for the posttranslational modification of eukaryotic elongation factor 2 (EEF2) that is the target of ADPRTs or by mutation of EEF2 itself. We show that engineering resistance to ADPRTs, one of the most potent toxins acting on human cells, is essential to achieve robust function of armored effector cell lines. This work establishes a critical step on the path to equip effector cells with the ability to deliver powerful toxins to cancer cells and introduces a platform to investigate extension to primary autologous or allogeneic therapeutic cell types.